Fresh Voices on Extensive Reading: A Narrative Study of Indonesian University Students - Wahyu Wienanda; Anik Nunuk Wulyani; Francisca Maria Ivone (Didaktika: Jurnal Kependidikan, 2025)
Extensive reading (ER) is an instructional approach to reading pedagogy that helps to encourage students to engage in a large amount of reading without being burdened by the concept of being assessed. The purpose of this study is to investigate university-level students’ perceptions of how the implementation of extensive reading inside their classroom and their suggestions about the implementation of extensive reading inside their classroom. Qualitative research was used as the design of this study, consisting of 3 freshman students of one University in Malang, East Java, Indonesia, as the participants. The research data was collected through interviews of those students, and the interview was recorded and transcribed by the researcher. The data was analyzed using narrative analysis based on the data collected from the interview conducted before. The analyses revealed that students’ perceptions towards the implementation of extensive reading are mostly positive, and students suggested that the task should be changed or removed. The study provides implications for the lecturer to carefully implement extensive reading as an approach to help students learn to read and build their reading habits. The lecturers should also sufficiently analyze and implement the characteristics of extensive reading in order to fully optimize the implementation of extensive reading in the classroom.